Strategy Formulation of Natural Gas Continuity Supply (Case Study PT ABC) - Dhanu Saptowulan; Idqan Fahmi; Bagus Sartono (Testing Center for Oil and Gas LEMIGAS, 2022)
This study aims to formulate a strategy for PT ABC in maintaining the continuity of natural gas supply. Feasibility analysis and decision tree method are used to determine the chosen strategy in maintaining the continuity of natural gas supply. Internal and external analysis are used to identify the key success factors of the company in implementing the chosen strategy and then summarized and evaluated using IFE and EFE matrix. To formulate implementation strategies by aligning key internal and external factors, IE and SWOT matrix are used. QSPM matrix is used to determine the priority of the implementation strategy. The results show IFE and EFE score are 2.55 and 2.76 respectively, so that PT ABC has suffi cient internal resources to maintain the continuity of natural gas supply and able to respond well to opportunities and threats. This condition can be managed best with hold and maintain strategies which are market penetration and product development. QSPM Matrix analysis show that product development group strategy has the highest Total Attractiveness Score (TAS) thus become priority to be executed and then market penetration strategy.